Improving Student Self-awareness of Cyberbullying Victims Through Reality Counseling Services - Aulia, Fitri; Ketut Suarni, Ni; Ketut Gading, I; Kerti Nitiasih, Putu; Nanci Riastini, Putu (KnE Social Sciences, 2024)
Self-awareness is an individual process of recognizing oneself. However, this selfawareness does not mean that a person is swept away in the current of his emotions so that the mood completely dominates him. Both the victim and the perpetrator. This study aims to determine the increase in student self-awareness of cyberbullying victims through reality counseling services. Counseling with a reality approach, using WDEP methods (Wants, Direction, Evaluation, Planning) helps individuals become rational and mentally strong. The participants in this study were students at SMP N 2 Selong who had experienced acts of cyberbullying and were declared to be in a psychologically disturbed situation. The study used an experimental method using a single case experimental design. The results showed that from a series of reality counseling assessment processes, such as counseling interviews, the subjects showed positive changes in the formation of self-awareness. Keywords: cyberbullying, self-awareness, reality counseling